Ways of optimizing central executive bodies with special status in the context of administrative reform - Kolesnik, I. I. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
The article is devoted to problems of the investigative experiment to establish the individual elements of the mechanism of the accident and its relations with the examinations. It was noted that the implementation of the investigative experiment is an extremely important action, because of its material (the results) are required to conduct a situational engineering and transport expertise accident circumstances. It is proved that the main problem and challenge the investigative experiment is to establish the individual elements of the mechanism of the accident (apparently, the possible existence of certain phenomena, determination of braking, etc.), which, in turn, requires mandatory participation in the appropriate specialist.